Study of Radiative Defects Using Current-Voltage Characteristics in ZnO Rods Catalytically Grown on 4H-p-SiC. (11th July 2010) - Bano, N.; Hussain, I.; Nur, O.; Willander, M.; Klason, P.
Abstract : High-quality ZnO rods were grown by the vapour-liquid-solid (VLS) technique on 4H-p-SiC substrate. The current transport mechanisms of the diodes at room temperature (RT) have been explained in term of the space-charge-limited current model based on the energy band diagram of ZnO rods/4H-p-SiC heterostructure. The tunneling mechanism via deep-level states was found to be the main conduction process at low-applied voltage but at trap-filled limit voltageV TFL all traps are filled and the space-charge-limited current conduction dominated the current transport. From the RT current voltage measurements, the energy of the deep level trap and the trap concentration were obtained as~ 0.24 ± 0.02  eV and4.4 × 10 18 cm −3, respectively. The deep level states observed correspond to zinc interstitial (Zn i ), responsible for the violet emission.